PENGARUH KECERDASAN EMOSIONAL DAN KESEJAHTERAAN SUBYEKTIF TERHADAP KINERJA MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Pravidaningrum, Nur Latifa Hanim; Rizana, Dani (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Gombong, 2023)
This writing aims to analyze the effect of emotional intelligence, subjective well-being on performance through job satisfaction as an intervening variable in Kindergarten Teachers in Karanggayam District. The independent variables in this study are emotional intelligence and subjective well-being, while the dependent variable is performance, and the intervening variable is job satisfaction. The data collection technique in this study is non-probability sampling with saturated sampling technique, where all the population is sampled as many as 52 respondents. The hypothesis was tested with the help of the SPSS 25.0 for windows program. The method used is a quantitative method using multiple linear regression analysis. Based on the t test, emotional intelligence variables, subjective well-being have a positive effect on performance and job satisfaction. Meanwhile, based on the Sobel test, job satisfaction variables can mediate between emotional intelligence and subjective well-being on performance